Mycosporine-Like Amino Acids (MAAs) Profile of cyanobacteria from Different Historical Kunds of Varanasi, India - Mishra, Sonal; Pandey, Abha; Ahmed, Haseen; Kumar, Deepak; Singh, Vidya; Sinha, Rajeshwar P. (International Journal of Applied Sciences and Biotechnology, 2019)
Copious facts have demonstrated that UV radiation is harmful to cyanobacteria. Sun-screening compounds such as mycosporine-like amino acids (MAAs) protect these organisms from deleterious UV radiation. MAAs absorb UV radiation in the range of 310 to 362 nm. These natural sunscreens obtained from cyanobacteria are excellent alternative to present day synthetic UV filters. In the present study, several cyanobacteria were collected from six historical Kunds of Varanasi, India. MAAs profile of these cyanobacteria was recorded with the help of UV-Vis spectroscopy, High performance liquid chromatography (HPLC) and Fourier transform infrared (FTIR) analysis. Various MAAs were identified as Porphyra-334 (λmax = 334 nm), Palythine (λmax = 320 nm), Asterina-330 (λmax = 330 nm), Mycosporine-glycine (λmax =310 nm) and Mycosporine-methylamine-serine (λmax =327 nm) having retention times (RT) of 3.62, 1.65, 1.53, 2.55 and 1.51 min, respectively, obtained from different cyanobacteria (Microcystis aeruginosa, Anabaenopsis sp., Merismopedia sp., Aulosira fertilissima, Rivularia sp., Phormidium sp., Nostoc sp. and Stigonema sp.). It is concluded that these MAAs from different historical Kunds may provide protection to the cyanobacteria growing thereof from the adverse effect of harmful UV radiation. MAAs are considered to be potential bioactive compounds that are highly intriguing from biotechnological perspective. Int. J. Appl. Sci. Biotechnol. Vol 7(3): 317-326